THE EFFECTIVENESS OF USING HADITH VALIDITY CRITERIA IN PROVING THE TRUTH OF NEWS - Abdulloh Ulin Nuha; Ahmad Fudhaili (SOSIOEDUKASI, 2026)
The rapid expansion of digital communication has accelerated the dissemination of information while increasing the spread of misinformation, disinformation, and fake news. Although contemporary journalism employs various fact-checking mechanisms, limited attention has been given to the potential contribution of classical Islamic scholarship to modern information verification. This study examines the applicability of hadith validity criteria as a conceptual framework for verifying the credibility of digital news. A qualitative library research approach was employed through the analysis of classical hadith literature and contemporary studies on journalism, digital media, and information verification. The findings indicate that the five criteria of hadith validity ittisal al-sanad, 'adalah, dhabt, shudhudh, and 'illah can be operationalized as sequential indicators for identifying information sources, assessing source credibility, verifying factual accuracy, conducting cross-verification, and detecting hidden inconsistencies. These criteria collectively establish a multi-layered verification model that integrates technical verification with ethical accountability. The novelty of this study lies in reconceptualizing classical hadith authentication as an interdisciplinary framework that bridges Islamic epistemology and contemporary communication studies. The proposed framework contributes to media literacy by providing an ethically grounded approach that complements existing fact-checking practices and supports more responsible information verification in the digital era.